FGF1 and IGF1-conditioned 3D culture system promoted the amplification and cancer stemness of lung cancer cells. (December 2017) - Liu, Pengpeng; Zhang, Rui; Yu, Wenwen; Ye, Yingnan; Cheng, Yanan; Han, Lei; Dong, Li; Chen, Yongzi; Wei, Xiyin; Yu, Jinpu
Abstract: Lung cancer stem cells (LCSCs) are considered as the cellular origins of metastasis and relapse of lung cancer. However, routine two-dimensional culture system (2D-culture) hardly mimics the growth and functions of LCSCs in vivo and therefore significantly decreases the stemness activity of LCSCs. In this study, we constructed a special BME-based three-dimensional culture system (3D-culture) to amplify LCSCs in human lung adenocarcinoma cell line A549 cells and found 3D-culture promoted the enrichment and amplification of LCSCs in A549 cells displaying higher proliferation potential and invasion activity, but lower apoptosis. The expression and secretion levels of FGF1 and IGF1 were dramatically elevated in 3D-culture compared to 2D-culture. After growing in FGF1 and IGF1-conditioned 3D-culture, the proportion of LCSCs with specific stemness phenotypes in A549 cells significantly increased compared to that in conventional 3D suspension culture system. Further results indicated that FGF1 and IGF1 promoted the amplification and cancer stemness of LCSCs dependent on MAPK signaling pathway. Our data firstly established a growth factors-conditioned 3D-culture for LCSCs and demonstrated the effects of FGF1 and IGF1 in promoting the enrichment and amplification of LCSCs which might provide a feasible cell model in vitro for both mechanism study and translational research on lung cancer.